Low‐dose BMP‐2 and MSC dual delivery onto coral scaffold for critical‐size bone defect regeneration in sheep. Issue 12 (26th April 2017) - Decambron, Adeline; Fournet, Alexandre; Bensidhoum, Morad; Manassero, Mathieu; Sailhan, Frédéric; Petite, Hervé; Logeart‐Avramoglou, Delphine; Viateau, Véronique
ABSTRACT: Tissue‐engineered constructs (TECs) combining resorbable calcium‐based scaffolds and mesenchymal stem cells (MSCs) have the capability to regenerate large bone defects. Inconsistent results have, however, been observed, with a lack of osteoinductivity as a possible cause of failure. This study aimed to evaluate the impact of the addition of low‐dose bone morphogenetic protein‐2 (BMP‐2) to MSC‐coral‐TECs on the healing of clinically relevant segmental bone defects in sheep. Coral granules were either seeded with autologous MSCs (bone marrow‐derived) or loaded with BMP‐2. A 25‐mm‐long metatarsal bone defect was created and stabilized with a plate in 18 sheep. Defects were filled with one of the following TECs: (i) BMP ( n  = 5); (ii) MSC ( n  = 7); or (iii) MSC‐BMP ( n  = 6). Radiographic follow‐up was performed until animal sacrifice at 4 months. Bone formation and scaffold resorption were assessed by micro‐CT and histological analysis. Bone union with nearly complete scaffold resorption was observed in 1/5, 2/7, and 3/6 animals, when BMP‐, MSC‐, and MSC‐BMP‐TECs were implanted, respectively. The amount of newly formed bone was not statistically different between groups: 1074 mm 3 [970–2478 mm 3 ], 1155 mm 3 [970–2595 mm 3 ], and 2343 mm 3 [931–3276 mm 3 ] for BMP‐, MSC‐, and MSC‐BMP‐TECs, respectively. Increased scaffold resorption rate using BMP‐TECs was the only potential side effect observed. In conclusion, although the dual delivery of MSCs and BMP‐2 onto a coral scaffold further increased bone formation and bone union when compared to single treatment, results were non‐significant. Only 50% of the defects healed, demonstrating the need for further refinement of this strategy before clinical use. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2637–2645, 2017. Abstract : The addition of low‐dose BMP‐2 to MSC‐coral‐based tissue‐engineered constructs (TECs) may overcome the inconsistent results seen during healing of large defects in bone. Eighteen sheep underwent a 25‐mm‐long bone resection filled with BMP‐, MSC‐, or MSC‐BMP‐TECs. At 4 months postoperatively, MSC‐BMP‐TECs induced the highest union rate. Although the MSC‐BMP dual delivery further increased bone formation and bone union when compared to single treatment, results were both non‐significant and inconsistent with only 50% of the defects that healed.